Post-pandemic conceptual study on Virtual Learning Method (VLM) in chemical engineering-related courses / Syafiza Abd Hashib ... [et al.] - Abd Hashib, Syafiza; Marpani, Fauziah; Md Zaki, Nurul Asyikin; Abdullah, Aidora (Universiti Teknologi MARA, Kedah, 2024)
Virtual learning in chemical engineering employs digital technologies and online platforms, including virtual classrooms, simulations, and collaborative tools, to deliver educational content and interactive experiences. This approach offers flexibility in time and location, enabling students to access course materials, simulations, and projects, fostering an understanding of chemical engineering principles. It replicates traditional learning while providing remote engagement and assessments, ensuring specific learning goals are met. In the wake of the global pandemic, this paper explores the conceptual shift to virtual learning in chemical engineering. In considering the relationship between technology and education, evaluating the advantages and constraints of virtual learning approaches is crucial. Although technology has undeniable potential to improve accessibility and student involvement, it is vital to ensure that its implementation aligns with the specific needs and educational goals of chemical engineering. The study examines benefits, challenges, and student experiences during this transition, shedding light on efficacy, engagement impact, and perceptions regarding complex subjects like chemical engineering. By analyzing the literature review and integrating it into the conceptual learning method, the paper offers insights into the post-pandemic education landscape, informing educators and institutions about the viability of virtual learning approaches and providing suggestions for enhancing their implementation in chemical engineering curricula.